NOUNS: A STUDY OF THEIR GRAMMATICAL CHARACTERISTICS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the different grammatical categories of nouns, such as number, gender, case, countability, and others, highlighting their role in the structure and function of language. It explains how nouns can be singular or plural, masculine, feminine, or neuter, and their use in different syntactical roles like subject, object, and possessive. The article also covers the distinction between concrete and abstract nouns, as well as proper and common nouns. It emphasizes how these categories influence sentence formation and clarity in communication. Through a detailed examination, the article serves as a foundational guide for understanding the grammatical flexibility and importance of nouns in both written and spoken language.